Redox regulation of adventitious root formation through downstream changes in hormonal system in mung bean [Vigna radiata (L.) R. Wilczek] - Durga Kora; Soumen Bhattacharjee (Annals of Systems Biology - Peertechz Publications, 2021)
Redox regulation on plant morphogenetic process of Adventitious Rooting (AR) can be vouched from the experimental data of redox manipulated salicylic acid treated hypocotyl explants of mung bean. In our previous work, application of pro-oxidant H2O2 (500 µM) followed by salicylic acid (SA, 600 µM) have been shown to significantly augment Adventitious Root Formation (ARF), whereas 10 ×10-4 M DPI (Diphenyleneiodonium, an inhibitor of NADPH-oxidase) - 600 µM SA and 10×10-4 M (Dimethylthiourea, a free radical scavenger) - 600 µM SA combination reduced the formation of ARF in hypocotyl explants of mung bean. In the present study, we have examined the impact of such treating conditions or redox manipulation on changes in endogenous titer of bonafide hormone system (gibberelic acid, abscisic acid, jasmonic acid) to document ROS- hormone interaction during adventitious rooting. The work suggests signinificant impact of redox manipulation on changes in endogenous titer of these hormonal system associated with AR. 500 µM H2O2 - 600 µM SA treatment combination, which has augmented formation of AR, has also shown higher accumulation of these hormones as compared to the untreated control. Further, DPI with or without combination of SA which inhibited the ARF, has also reduced the endogenous concentration of these Plant Growth Regulators (PGRs), suggesting role of these growth regulators in low concentration on adventitious root formation. Role of the SA signalling with prooxidant H2O2 as second messenger during AR is suggested.